Preparation method of molecular sieve coated noble metal-rare earth metal / TiO2 monolithic catalyst and application of molecular sieve coated noble metal-rare earth metal / TiO2 monolithic catalyst in CO oxidation
The molecular sieve is coated with precious metal-rare earth metal/TiO2 integral catalyst, and the domain-limiting effect of the molecular sieve and the electronic modulation of rare earth metals are used to solve the problems of sulfur poisoning and heavy metal poisoning in steel sintered flue gas, achieving efficient and economical CO oxidation effect.
Patent Information
- Application Number
- CN202510651087.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-08-22
- Estimated Expiration
- 2045-05-20
AI Technical Summary
Existing precious metal-loaded TiO2 catalysts are susceptible to COS sulfur poisoning and heavy metal poisoning in sintered steel flue gas, and the high amount of precious metals has led to high costs, making it difficult to achieve efficient and economical CO oxidation.
The molecular sieve is used to coat the precious metal-rare earth metal/TiO2 integral catalyst, and a molecular sieve coating layer is constructed on the surface of the TiO2 support through in situ hydrothermal method. The domain-limited channel of the molecular sieve is used to selectively intercept sulfur species and heavy metal ions, and the electronic modulation of rare earth metals is combined with the electron modulation of rare earth metals to optimize the electronic structure of precious metals to form a multi-scale synergistic effect.
It significantly improves the catalyst's anti-sulfur poisoning and heavy metal poisoning ability, reduces the amount of precious metals, improves CO oxidation performance and catalyst stability, and reduces operating costs.
Smart Images

Figure CN120515490A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of industrial catalysis and waste gas treatment, and in particular to a method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst and its application in CO oxidation reaction. Background Art
[0002] In recent years, CO pollution from typical industrial sources, particularly steel sintering processes, has become increasingly prominent, becoming a key factor hindering sustained improvements in environmental quality. CO not only directly harms human health through hemoglobin binding, but also participates in photochemical reactions, exacerbating the formation of complex atmospheric pollution such as ozone and secondary aerosols. Strengthening CO emission control has become a key task in improving the modern environmental governance system, and developing efficient and cost-effective CO purification technologies is a key path to achieving this goal.
[0003] CO catalytic oxidation technology is widely recognized as the preferred option for CO treatment in steel sintering flue gas due to its efficient reaction kinetics and wide adaptability. This technology reduces the reaction activation energy by utilizing active sites on the catalyst surface, enabling efficient oxidation of CO and O₂ at relatively low temperatures. In catalyst system design, precious metal-based catalysts have attracted considerable attention due to their excellent CO catalytic activity at low temperatures. Precious metal catalysts supported on TiO₂ exhibit significant advantages: TiO₂'s acidic, reducible properties, and abundant oxygen vacancies form strong metal-support interactions with the precious metal component, thereby enhancing oxygen activation efficiency and reaction stability. However, the large-scale application of precious metal-supported TiO₂ catalysts still faces multiple challenges. First, carbonyl sulfide (COS) in sintering flue gas forms a stable sulfur species adsorption layer with the precious metal active sites, leading to irreversible deactivation of the catalyst. Second, heavy metal vapors such as Pb and Zn deposit on the catalyst surface, covering the acidic sites and significantly inhibiting CO adsorption and activation efficiency. Furthermore, to achieve industrial-scale CO conversion rates, the precious metal loading is typically high, resulting in high catalyst costs. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst and its application in CO oxidation, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst, comprising: a composite active component composed of noble metal and rare earth metal, a TiO2 carrier, and a molecular sieve coating layer;
[0007] The composite active component composed of the noble metal and the rare earth metal is dispersed in the TiO2 carrier, and the molecular sieve coating layer coats the TiO2 carrier.
[0008] Furthermore, the precious metal is selected from at least one of Pt, Pd, Au and Ir, and the rare earth metal is at least one of La, Gd, Nd and Pr; the carrier is anatase TiO2; and the molecular sieve coating layer is composed of SAPO-18 or SAPO-34 molecular sieve.
[0009] Furthermore, the precious metal loading accounts for 0.2 to 1.5 wt.% of the mass of the TiO2 carrier, and the rare earth metal loading accounts for 0.2 to 2 wt.% of the mass of the TiO2 carrier.
[0010] The second technical solution of the present invention is to provide a method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst, comprising the following steps:
[0011] (1) A noble metal salt, a rare earth metal salt, and a titanium source are dissolved in a solvent, and after hydrolysis and aging, a binder is added to obtain a sol system; the solvent is preferably a mixed solvent of anhydrous ethanol and acetylacetone; wherein the acetylacetone acts as a chelating agent to stabilize the metal ions, prevent their premature precipitation, and slow down the hydrolysis rate of the titanium source to ensure uniform formation of the sol, while the anhydrous ethanol provides a suitable polar environment to promote dissolution;
[0012] (2) loading the sol system onto a ceramic support, followed by drying, solidification, and calcination to obtain a noble metal-rare earth metal / TiO2 matrix; preferably, vacuum impregnation is used for loading;
[0013] (3) In situ growth of a molecular sieve coating layer on the noble metal-rare earth metal / TiO2 substrate by a hydrothermal method, followed by stepwise calcination in an oxidizing atmosphere and a reducing atmosphere to obtain the molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst.
[0014] Furthermore, the precious metal salt is selected from at least one of chloroplatinic acid (H2PtCl6), palladium chloride (PdCl2), chloroauric acid (HAuCl4) and iridium chloride (IrCl3); the rare earth metal salt is selected from at least one of lanthanum nitrate (La(NO3)3), gadolinium nitrate (Gd(NO3)3), neodymium nitrate (Nd(NO3)3) and praseodymium nitrate (Pr(NO3)3).
[0015] Furthermore, the binder is at least one of silica sol, polyvinyl alcohol, polyethylene glycol and hydroxypropyl methylcellulose.
[0016] Furthermore, the drying and curing temperature in step (2) is 80-120° C., and the calcination temperature is 400-700° C.; the hydrothermal temperature in step (3) is 140-200° C., and the reaction time is 2-6 days.
[0017] Furthermore, in the staged roasting in step (3), the oxidizing atmosphere calcination conditions are: in an O2 / N2 mixed gas containing an oxygen volume fraction of 3% to 25%, the temperature is raised to 400 to 700°C, and the constant temperature roasting is carried out for 2 to 8 hours; the reducing atmosphere calcination conditions are: in an H2 / N2 mixed gas containing a hydrogen volume fraction of 1% to 7%, the temperature is raised to 400 to 700°C, and the constant temperature roasting is carried out for 2 to 8 hours.
[0018] Furthermore, the more specific steps of step (3) are as follows:
[0019] A silicon source, an aluminum source, a template, phosphoric acid, and water are mixed in a certain molar ratio and stirred evenly to prepare a molecular sieve initial gel, which is then loaded into the lining of a reactor. Subsequently, the noble metal-rare earth metal-loaded TiO2 matrix obtained in step (2) is placed in the molecular sieve initial gel and subjected to a hydrothermal reaction. After the hydrothermal reaction is completed, the resulting material is washed and dried, and then calcined in stages in an oxidizing and reducing atmosphere, respectively, to ultimately obtain a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst.
[0020] The silicon source is selected from at least one of sodium silicate, ethyl orthosilicate or silica sol; the aluminum source is selected from at least one of sodium metaaluminate, pseudoboehmite or aluminum sulfate; and the template is selected from at least one of tetraethylammonium hydroxide (TEAOH), morpholine (MOR), triethylamine (TEA), N,N-diisopropylethylamine (DIPEA) and N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (DMPDOH).
[0021] Furthermore, the molar ratio of Si:Al:P:H2O:template is 1-5:4-14:2-16:80-200:3-10.
[0022] Furthermore, the molecular sieve material is SAPO-18 or SAPO-34.
[0023] The present invention proposes to prepare a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst by an in-situ hydrothermal method. This technology effectively solves the problems of COS sulfur poisoning deactivation, heavy metal poisoning deactivation and economic bottleneck faced by noble metal / TiO2 catalysts in the process of steel sintering flue gas purification through the multi-scale synergistic effect of electronic modulation of active components and molecular sieve confinement effect. Specifically, first, the unique pore structure and acidic properties of the molecular sieve limit the adsorption and diffusion of sulfur species through the confinement effect, effectively fixing them on the surface of the molecular sieve, avoiding direct contact between sulfide and noble metal active centers, thereby significantly improving the catalyst's resistance to sulfur poisoning. Secondly, the acidic sites on the surface of the molecular sieve can preferentially adsorb and fix heavy metal ions, forming a steric hindrance protective layer, reducing the coverage and poisoning effect of heavy metals on the noble metal active sites, and effectively delaying the deactivation process of the catalyst. Furthermore, rare earth metals regulate the electronic structure of noble metals through the electron transfer effect, optimize their d-band center energy levels, and enhance the oxygen activation ability of the noble metal surface. While reducing the use of precious metals, the addition of rare earth metals not only improves the catalyst's low-temperature oxidation efficiency but also significantly enhances its overall catalytic performance. This multi-stage synergistic strategy systematically addresses the economic bottlenecks of traditional catalysts caused by poisoning and deactivation and excessive precious metal loading while maintaining high catalyst activity. This provides a technical solution for complex flue gas purification systems that combines long-term stability with industrial feasibility.
[0024] The third technical solution of the present invention is to provide the application of the above-mentioned molecular sieve-coated noble metal-rare earth metal / TiO2 integral catalyst in the carbon monoxide oxidation reaction.
[0025] The fourth technical solution of the present invention: provides a CO catalytic oxidizer, comprising the above-mentioned molecular sieve-coated precious metal-rare earth metal / TiO2 integral catalyst.
[0026] The fifth technical solution of the present invention: provides an exhaust gas treatment system for a steel sintering machine, comprising the above-mentioned CO catalytic oxidizer.
[0027] The present invention is based on a multi-scale collaborative regulation strategy: a molecular sieve coating is constructed on the surface of precious metal-rare earth metal / TiO2 by an in-situ hydrothermal method, and the confined pores of the molecular sieve are used to selectively intercept sulfur species and heavy metal ions, blocking their contact with the active center; rare earth metals optimize the electronic structure of precious metals through electronic modulation, thereby improving oxygen activation capacity and reducing precious metal loading; the integral carrier design is combined with the mass transfer optimization characteristics of the molecular sieve coating to achieve the synergy of high mechanical strength and long-term catalytic performance in complex flue gas environments. This technology not only significantly improves the catalyst's resistance to sulfur and heavy metal poisoning, but also breaks through the economic bottleneck through the efficient use of active components, providing an efficient, stable and low-cost solution for the collaborative purification of multiple pollutants under harsh working conditions such as steel sintering flue gas.
[0028] The present invention has the following technical advantages:
[0029] (1) The present invention proposes a method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst. The method is simple to operate, easy to repeat, and has good controllability and consistency, aiming to optimize the CO catalytic oxidation performance.
[0030] Compared with Pt / TiO2 (ignition temperature T 70 =225℃)、Pt-Pr / TiO2(T 70 =220℃) and SAPO-34@Pt / TiO2(T 70 =216 ° C) catalyst, the ignition temperature T of the molecular sieve-coated precious metal-rare earth metal catalysts (SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2 and SAPO-18@Ir-La / TiO2) provided by the present invention is 70 The CO oxidation performance of the catalyst was improved by the synergistic effect of the molecular sieve coating and the bimetallic effects of precious metals and rare earth metals. This is mainly because the microporous structure of SAPO-34 and SAPO-18 molecular sieves improves the dispersion of precious metals (Pt, Pd, Au or Ir) and rare earth metals (Pr, Nd, Gd or La) through confinement. In addition, the strong acidic sites of the molecular sieves contribute to the adsorption and activation of CO. At the same time, the rare earth metals significantly enhance the redox ability of the precious metals through electronic and structural effects, while the oxygen storage capacity of the rare earth metals themselves accelerates the interfacial reaction between CO and O2. It is worth noting that the molecular sieve layer effectively inhibits the migration and agglomeration of active components through physical confinement, thereby maintaining the high activity of the catalyst over a wide temperature range.
[0031] After the introduction of COS in the reaction or the catalyst experienced Pb heavy metal poisoning, the ignition temperature T of SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, SAPO-18@Ir-La / TiO2, Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts was significantly decreased. 70The CO oxidation activity of all catalysts decreased to varying degrees when the temperature was increased to 222°C or 217°C, 217°C or 212°C, 229°C or 224°C, 237°C or 230°C, 281°C or 255°C, 263°C or 248°C, and 244°C or 238°C, respectively. The molecular sieve-coated noble metal-rare earth metal catalysts exhibited significantly superior resistance to COS and Pb poisoning than the other catalysts. This is primarily due to the following synergistic mechanism: the microporous structures of SAPO-34 and SAPO-18 selectively block large molecular poisons (such as sulfur or Pb species) from accessing the catalyst's active sites through a size-sieving effect, while allowing small molecules of CO / O2 to diffuse freely, thereby mitigating direct coverage of the noble metal surface by poisons. The rare earth metals possess oxygen storage-release functionality, dynamically scavenging adsorbed sulfur / lead species and forming stable sulfates or lead oxides, which then migrate to the support surface, avoiding clogging the noble metal active sites. Furthermore, electron transfer between the noble metal and the rare earth metal maintains the noble metal in its reduced state, effectively inhibiting poison-induced oxidative deactivation of active sites. The weak hydrophobicity of SAPO-18 or SAPO-34 reduces the adsorption tendency of polar poisons on the catalyst surface. Simultaneously, bimetallic loading further weakens the chemical adsorption strength of poisons through competitive adsorption (e.g., CO preferentially occupies active sites). In contrast, uncoated Pt / TiO2 and Pt-Pr / TiO2 catalysts lack both a physical barrier and synergistic chemical protection, allowing poisons to directly coat the active metal surface, leading to irreversible passivation. While SAPO-34@Pt / TiO2 possesses the physical barrier of a molecular sieve, it only supports a single Pt metal and lacks the oxygen buffering effect of a rare earth metal, making it unable to dynamically remove adsorbed poisons. Furthermore, due to the lack of sufficient electronic effects, its competitive adsorption capacity is weak, making it more likely for poisons to occupy isolated Pt sites. These factors contribute to its significantly weaker anti-poisoning ability than bimetallic systems (e.g., SAPO-34@Pt-Pr / TiO2). These results further demonstrate the importance of molecular sieve coating and noble metal-rare earth metal co-design in improving poisoning resistance. This design provides a solution that combines high activity and poisoning resistance for the purification of industrial sulfur- and heavy metal-containing waste gases.
[0032] (2) The present invention proposes a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst prepared by an in-situ hydrothermal method. The catalyst adopts a coupling design of noble metal-rare earth metal electronic synergy and molecular sieve confinement protection to systematically solve key problems such as COS sulfur poisoning, heavy metal (Pb, Zn) poisoning and high cost of noble metal use in steel sintering flue gas. First, noble metals and rare earth metals are in-situ loaded on the surface of the TiO2 carrier to form a dual-active component system. Noble metals serve as the main active center for CO oxidation. Rare earth metals optimize the d-band center position of noble metals through the electron transfer effect, effectively reducing the adsorption energy and dissociation energy barrier of CO and improving its reaction activity. At the same time, the oxygen vacancies of rare earth metals promote the adsorption and activation of O2. In addition, rare earth metals inhibit the high-temperature migration of noble metal nanoparticles through anchoring, solving the problem of activity decay caused by sintering of traditional catalysts. Subsequently, a hydrothermal crystallization process is used to in-situ grow a SAPO-34 or SAPO-18 molecular sieve coating layer on the noble metal-rare earth metal / TiO2 surface. The microporous structure of the molecular sieve provides a size screening effect, which can selectively block large-sized poison molecules (such as sulfides and lead compounds) from entering the catalyst, and only allow small molecules (such as CO and O2) to diffuse freely to the active sites, thereby improving the catalyst's anti-poisoning ability. The acidic sites can preferentially adsorb and fix heavy metal ions, forming a steric hindrance protective layer, which effectively prevents them from covering the noble metal active centers and further delays the catalyst deactivation process. It is worth noting that under the electronic regulation of rare earth metals, the activity of noble metals is enhanced, so that the amount of noble metals required while maintaining the same CO conversion rate is significantly reduced, and the atomic utilization efficiency is significantly improved. Through the synergistic effect of the physical shielding effect provided by the molecular sieve coating and the structural stabilization of the rare earth metal, the service life of the catalyst in simulated steel sintering flue gas is significantly extended, and the overall operating cost is reduced. In summary, the catalyst prepared by the present invention has high activity, excellent anti-toxic performance, thermal stability and economy, and provides a high-efficiency, low-consumption, long-term and stable solution for the catalytic oxidation of CO and purification of harmful impurities in steel sintering flue gas.
[0033] The present invention discloses the following technical effects:
[0034] The molecular sieve-coated precious metal-rare earth metal / TiO2 monolithic catalyst provided by the present invention has significant technical effects in the following aspects: (1) Strong anti-poisoning ability. The molecular sieve microporous structure blocks sulfur species, heavy metals and other poisons from contacting the active sites through size screening. The oxygen storage-release function of the rare earth metal can dynamically remove poisons. The bimetallic system can also maintain the reduced state of the precious metal, weaken the adsorption of poisons, and effectively solve the problems of COS sulfur poisoning and heavy metal poisoning. (2) High catalytic activity. The molecular sieve confinement effect improves the metal dispersion. The rare earth metal optimizes the electronic structure of the precious metal, enhances the oxygen activation ability, and reduces the CO oxidation ignition temperature. (3) Good economic efficiency. While maintaining high activity, the amount of precious metal used is reduced, reducing costs. (4) The molecular sieve layer can also inhibit the migration and agglomeration of active components and improve the thermal stability of the catalyst.
[0035] The catalyst provided by the present invention not only performs well in terms of anti-poisoning ability and catalytic activity, but also has good economy and thermal stability, providing a highly potential technical solution for industrial applications in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 X-ray diffraction (XRD) patterns of SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, SAPO-18@Ir-La / TiO2, Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3.
[0038] Figure 2 CO oxidation conversion rate diagram of SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, SAPO-18@Ir-La / TiO2, Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3.
[0039] Figure 3This is a graph showing the CO oxidation conversion rates of SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, SAPO-18@Ir-La / TiO2, Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 in the presence of 500 ppm COS.
[0040] Figure 4 This is a graph showing the CO oxidation conversion rates of SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, SAPO-18@Ir-La / TiO2, Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 after being poisoned with 4 wt.% Pb. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in this field and are not the focus of the present invention.
[0047] In the first aspect of the present invention, a molecular sieve-coated precious metal-rare earth metal / TiO2 integral catalyst is provided, comprising: a composite active component composed of precious metals and rare earth metals, a TiO2 carrier, and a molecular sieve coating layer; the composite active component composed of precious metals and rare earth metals is dispersed in the TiO2 carrier, and the molecular sieve coating layer coats the TiO2 carrier.
[0048] Among them, the precious metal active component is preferably at least one of Pt, Pd, Au and Ir, and the rare earth metal component is preferably at least one of La, Gd, Nd and Pr; the carrier is anatase TiO2; and the molecular sieve coating layer is composed of SAPO-18 or SAPO-34 molecular sieve.
[0049] In a second aspect of the present invention, a method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst is provided, comprising the following steps:
[0050] (1) A titanium source, a noble metal salt, and a rare earth metal salt are dissolved in a mixed solvent of anhydrous ethanol and acetylacetone. A nitric acid aqueous solution is slowly added dropwise at a constant temperature of 40 to 80°C with stirring to initiate a hydrolysis reaction. The reaction time is controlled to be 2 to 6 hours. After the hydrolysis reaction is complete, the system is placed at room temperature and aged for 6 to 24 hours to form a stable sol system. Finally, an appropriate amount of binder is added and stirring is continued for 0.5 to 2 hours to obtain a uniform sol system with an appropriate viscosity.
[0051] (2) A cordierite honeycomb ceramic support (200-400 mesh) is placed in a vacuum impregnation apparatus, and the TiO2 sol prepared in step (1) is fully infiltrated into the pores of the support by negative pressure. After the impregnation is completed, the vacuum is released, and the support loaded with the sol is dried at 80-120°C for 6-12 hours, and then the temperature is programmed to 400-700°C at a heating rate of 2-5°C / min and calcined for 3-8 hours to obtain a noble metal-rare earth metal loaded TiO2 monolithic catalyst.
[0052] (3) The silicon source (in terms of Si), the aluminum source (in terms of Al), the phosphoric acid (in terms of P), water and the template are mixed in a molar ratio of 1-5:4-14:2-16:80-200:3-10, stirred thoroughly to form an initial molecular sieve gel, and transferred to the lining of the reactor. Subsequently, the noble metal-rare earth metal supported TiO2 monolithic catalyst prepared in step (2) is immersed in the initial molecular sieve gel and subjected to a hydrothermal crystallization reaction at 140-200°C for 2-6 days. After the hydrothermal reaction is completed, the product is washed and dried, and then heated to 400-700°C in an O2 / N2 mixed gas containing an oxygen volume fraction of 3% to 25%, and calcined at a constant temperature for 2-8 hours; and heated to 400-700°C in an H2 / N2 mixed gas containing a hydrogen volume fraction of 1% to 7%, and calcined at a constant temperature for 2-8 hours. Finally, a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst was obtained.
[0053] Preferably, in step (1), the precious metal salt is selected from chloroplatinic acid (H2PtCl6), palladium chloride (PdCl2), chloroauric acid (HAuCl4) or iridium chloride (IrCl3); the rare earth metal salt is selected from lanthanum nitrate (La(NO3)3), gadolinium nitrate (Gd(NO3)3), neodymium nitrate (Nd(NO3)3) or praseodymium nitrate (Pr(NO3)3); the binder is silica sol, polyvinyl alcohol, polyethylene glycol or hydroxypropyl methylcellulose.
[0054] Preferably, in step (2), the drying and curing temperature is 80-120°C, and the calcining temperature is 400-700°C.
[0055] Preferably, in step (3), the silicon source is selected from sodium silicate, tetraethyl orthosilicate, or silica sol; the aluminum source is selected from sodium metaaluminate, pseudoboehmite, or aluminum sulfate; the template is selected from tetraethylammonium hydroxide (TEAOH), morpholine (MOR), triethylamine (TEA), N,N-diisopropylethylamine (DIPEA), or N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (DMPDOH). The molecular sieve is SAPO-18 or SAPO-34.
[0056] In some embodiments, the precious metal salt used in step (1) is chloroplatinic acid (H2PtCl6), palladium chloride (PdCl2), chloroauric acid (HAuCl4) or iridium chloride (IrCl3); the rare earth metal salt is lanthanum nitrate (La(NO3)3), gadolinium nitrate (Gd(NO3)3), neodymium nitrate (Nd(NO3)3) or praseodymium nitrate (Pr(NO3)3); the binder is silica sol, polyvinyl alcohol, polyethylene glycol or hydroxypropyl methylcellulose.
[0057] In some embodiments, the drying and curing temperature in step (2) is 80-120°C, and the calcining temperature is 400-700°C.
[0058] In some embodiments, the silicon source in step (3) is sodium silicate, tetraethyl orthosilicate, or silica sol; the aluminum source is selected from sodium metaaluminate, pseudoboehmite, or aluminum sulfate; the template is tetraethylammonium hydroxide (TEAOH), morpholine (MOR), triethylamine (TEA), N,N-diisopropylethylamine (DIPEA), or N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (DMPDOH). The molecular sieve is SAPO-18 or SAPO-34.
[0059] The third aspect of the present invention provides the use of a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst in a carbon monoxide oxidation reaction.
[0060] In a fourth aspect, the present invention provides a CO catalytic oxidizer comprising the above-mentioned molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst.
[0061] In a fifth aspect, the present invention provides an exhaust gas treatment system for a steel sintering machine, comprising the above-mentioned CO catalytic oxidizer.
[0062] Example 1
[0063] A method for preparing a SAPO-34-coated Pt-Pr / TiO2 catalyst comprises the following steps:
[0064] (1) 42.7 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.191 g of chloroplatinic acid (H2PtCl6·6H2O) and 0.222 g of praseodymium nitrate (Pr(NO3)3·6H2O) were added under constant temperature and stirring at 60°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 4 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 12 hours for aging to form a stable sol. Finally, 2 g of silica sol was added as a binder and stirring was continued for 1 hour to obtain a uniform sol system.
[0065] (2) Place a cordierite honeycomb ceramic support (300 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate the air and maintain the vacuum for 5 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 100°C for 8 hours. Subsequently, heat the sample to 550°C at a heating rate of 2°C / min and calcine at this temperature for 5 hours to obtain a Pt-Pr / TiO2 monolithic catalyst.
[0066] (3) 2.24 g of sodium silicate, 2.15 g of pseudo-boehmite, 4.46 g of tetraethylammonium hydroxide, 4.49 g of phosphoric acid, and 15.71 g of water were mixed and stirred for 2 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Pt-Pr / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 180°C for 5 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 80°C for 12 hours. Finally, the dried sample was heated to 550°C in a 10% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 5 hours, then switched to a 3% H2 / N2 atmosphere and calcined under the same conditions for 4 hours to obtain a SAPO-34-coated Pt-Pr / TiO2 monolithic catalyst (labeled as SAPO-34@Pt-Pr / TiO2) with a Pt loading of 0.6 wt.% of the TiO2 mass and a Pr loading of 0.6 wt.% of the TiO2 mass.
[0067] Comparative Example 1
[0068] This comparative example differs from Example 1 in that the Pt / TiO2 monolithic catalyst was not coated with SAPO-34 molecular sieve and was not doped with Pr metal. All other conditions were identical to those in Example 1. Ultimately, a Pt / TiO2 monolithic catalyst (labeled as Pt / TiO2) with a Pt loading of 0.6 wt.% based on the mass of the TiO2 was obtained.
[0069] Comparative Example 2
[0070] This comparative example differs from Example 1 in that the Pt-Pr / TiO2 monolithic catalyst was not coated with SAPO-34 molecular sieve. All other conditions were identical to those in Example 1. Ultimately, a Pt-Pr / TiO2 monolithic catalyst (labeled as Pt-Pr / TiO2) was obtained, with a Pt loading of 0.6 wt.% based on the mass of the TiO2 and a Pr loading of 0.6 wt.% based on the mass of the TiO2.
[0071] Comparative Example 3
[0072] This comparative example differs from Example 1 in that the SAPO-34-coated Pt / TiO2 monolithic catalyst was not loaded with Pr. All other conditions were identical to those in Example 1. Ultimately, a SAPO-34-coated Pt / TiO2 monolithic catalyst (labeled SAPO-34@Pt / TiO2) with a Pt loading of 0.6 wt.% based on the mass of the TiO2 was obtained.
[0073] Example 2
[0074] A method for preparing a SAPO-18 coated Pd-Nd / TiO2 catalyst comprises the following steps:
[0075] (1) 53.4 g of tetraisopropyl titanate was dissolved in a mixed solvent of 130 mL of anhydrous ethanol and 60 mL of acetylacetone. 0.125 g of palladium chloride (PdCl2) and 0.365 g of neodymium nitrate (Nd(NO3)3·6H2O) were added under constant temperature and stirring at 70°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 6 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 8 hours for aging to form a stable sol. Finally, 3 g of hydroxypropyl methylcellulose was added as a binder and stirring was continued for 0.5 hours to obtain a uniform sol system.
[0076] (2) Place the cordierite honeycomb ceramic support (300 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate the air and maintain the vacuum for 8 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 90°C for 6 hours. Subsequently, heat the sample to 600°C at a heating rate of 3°C / min and calcine at this temperature for 4 hours to obtain a Pd-Nd / TiO2 monolithic catalyst.
[0077] (3) 8.33 g of tetraethyl orthosilicate, 5.74 g of sodium aluminate, 10.34 g of N,N-diisopropylethylamine, 5.88 g of phosphoric acid, and 19.21 g of water were mixed and stirred for 2 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Pd-Nd / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 160° C. for 6 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 90° C. for 6 hours. Finally, the dried sample was heated to 600°C in a 15% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 4 hours, and then switched to a 5% H2 / N2 atmosphere and calcined under the same conditions for 4 hours to obtain a SAPO-18-coated Pd-Nd / TiO2 monolithic catalyst (labeled as SAPO-18@Pd-Nd / TiO2) with a Pd loading of 0.5 wt.% based on the mass of TiO2 and a Nd loading of 0.8 wt.% based on the mass of TiO2.
[0078] Example 3
[0079] A method for preparing a SAPO-34-coated Au-Gd / TiO2 catalyst comprises the following steps:
[0080] (1) 63.95 g of tetraisopropyl titanate was dissolved in a mixed solvent of 160 mL of anhydrous ethanol and 40 mL of acetylacetone. 0.288 g of chloroauric acid (HAuCl4·3H2O) and 0.258 g of gadolinium nitrate (Gd(NO3)3·6H2O) were added under constant temperature and stirring at 50°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 3 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 16 hours for aging to form a stable sol. Finally, 3.5 g of polyvinyl alcohol was added as a binder and stirring was continued for 1.5 hours to obtain a uniform sol system.
[0081] (2) Place the cordierite honeycomb ceramic support (400 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate the system and maintain the vacuum for 10 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 110°C for 7 hours. Subsequently, heat the sample to 650°C at a heating rate of 4°C / min and calcine at this temperature for 3 hours to obtain an Au-Gd / TiO2 monolithic catalyst.
[0082] (3) 1.82 g of silica sol, 20.53 g of aluminum sulfate, 6.11 g of morpholine, 7.84 g of phosphoric acid, and 27.13 g of water were mixed and stirred for 3 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Pt-Pr / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 200°C for 4 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 110°C for 7 hours. Finally, the dried sample was heated to 650°C in a 20% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 3 hours, and then switched to a 6% H2 / N2 atmosphere and calcined under the same conditions for 3 hours to obtain a SAPO-34-coated Au-Gd / TiO2 monolithic catalyst (labeled as SAPO-34@Au-Gd / TiO2) with an Au loading of 0.8 wt.% based on the mass of TiO2 and a Gd loading of 0.5 wt.% based on the mass of TiO2.
[0083] Example 4
[0084] A method for preparing a SAPO-18 coated Ir-La / TiO2 catalyst comprises the following steps:
[0085] (1) 71.20 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.257 g of iridium chloride (IrCl3·3H2O) and 0.561 g of lanthanum nitrate (La(NO3)3·6H2O) were added under constant temperature and stirring at 80°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the reaction was allowed to react for 5 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 20 hours for aging to form a stable sol. Finally, 4 g of polyethylene glycol was added as a binder and stirring was continued for 2 hours to obtain a uniform sol system.
[0086] (2) Place the cordierite honeycomb ceramic support (400 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate the air and maintain the vacuum for 15 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 80°C for 12 hours. Subsequently, heat the sample to 450°C at a heating rate of 5°C / min and calcine at this temperature for 7 hours to obtain an Ir-La / TiO2 monolithic catalyst.
[0087] (3) 2.44 g of sodium silicate, 1.83 g of pseudo-boehmite, 6.96 g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide, 4.90 g of phosphoric acid, and 16.22 g of water were mixed and stirred for 4 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Ir-La / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 150° C. for 6 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 80° C. for 12 hours. Finally, the dried sample was heated to 450°C in a 25% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 7 hours, and then switched to a 2% H2 / N2 atmosphere and calcined under the same conditions for 7 hours to obtain a SAPO-18-coated Ir-La / TiO2 monolithic catalyst (labeled as SAPO-18@Ir-La / Ti) with an Ir loading of 0.7 wt.% based on the mass of TiO2 and a La loading of 0.9 wt.% based on the mass of TiO2.
[0088] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to XRD tests. The results are as follows: Figure 1As shown. SAPO-34-coated Pt-Pr / TiO2 exhibits typical characteristic diffraction peaks of anatase TiO2 and SAPO-34 molecular sieve; SAPO-18-coated Pd-Nd / TiO2 exhibits characteristic diffraction peaks of anatase TiO2 and SAPO-18 molecular sieve; SAPO-34-coated Au-Gd / TiO2 exhibits characteristic diffraction peaks of anatase TiO2 and SAPO-34 molecular sieve; SAPO-18-coated Ir-La / TiO2 exhibits characteristic diffraction peaks of anatase TiO2 and SAPO-18 molecular sieve. Pt / TiO2 and Pt-Pr / TiO2 only show diffraction peaks of anatase TiO2, while SAPO-34-coated Pt / TiO2 exhibits dual characteristic diffraction of anatase TiO2 and SAPO-34 molecular sieve. These results indicate that the molecular sieve coating layer was successfully constructed, and the coating process did not induce a phase change in the TiO2 or damage the molecular sieve structure. This demonstrates that the in situ hydrothermal synthesis coating process is compatible with the thermal stability of the TiO2 support. In addition, no characteristic diffraction peaks were observed for precious metals such as Pt, Pd, Au, and Ir, or rare earth metals such as La, Gd, Nd, or Pr, indicating that the metal active components are highly dispersed or that their nanoparticle size is smaller than the XRD detection limit.
[0089] The catalysts prepared in Examples 1-4 and Comparative Examples 1-3 were tested for their CO catalytic oxidation performance and COS poisoning resistance. The test conditions were: catalyst dosage 0.25 g (60-80 mesh), simulated flue gas composition of 1000 ppm CO, 10% H2O, 8% O2, 500 ppm COS (added as needed), reaction space velocity 150,000 h -1 .
[0090] The CO oxidation performance, COS poisoning resistance and Pb (4 wt.%) poisoning resistance test results of the catalyst are shown in Figure 2. Figure 2 、 Figure 3 and Figure 4 shown.
[0091] Depend on Figure 2It can be seen that compared with Pt / TiO2, Pt-Pr / TiO2, and SAPO-34@Pt / TiO2 catalysts, SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, and SAPO-18@Ir-La / TiO2 catalysts have higher CO catalytic oxidation performance. This is mainly because the microporous structure (~0.38nm) of SAPO-34 and SAPO-18 zeolites improves the dispersion of precious metals (Pt, Pd, Au, or Ir) and rare earth metals (Pr, Nd, Gd, or La) through confinement. In addition, the strong acidic sites of the zeolites facilitate the adsorption and activation of CO. At the same time, the rare earth metals significantly enhance the redox ability of the precious metals through electronic and structural effects, while the oxygen storage capacity of the rare earth metals themselves accelerates the interfacial reaction between CO and O2. It is worth noting that the molecular sieve layer effectively inhibits the migration and agglomeration of active components through the physical confinement effect, thereby maintaining the high activity of the catalyst over a wide temperature range.
[0092] Depend on Figure 3 and Figure 4It can be seen that after the introduction of COS or the catalyst was poisoned by heavy metal Pb, the CO oxidation activity of all catalysts decreased to varying degrees. However, the molecular sieve-coated noble metal-rare earth metal catalysts (SAPO-34@Pt-Pr / TiO2, SAPO-18@Pd-Nd / TiO2, SAPO-34@Au-Gd / TiO2, and SAPO-18@Ir-La / TiO2) showed significantly better resistance to COS and Pb poisoning than other catalysts. This is mainly due to the following synergistic mechanisms: (1) Physical barrier effect of the molecular sieve carrier: The microporous structure of SAPO-34 and SAPO-18 selectively blocks large molecular poisons (such as sulfur species or Pb species) from contacting the active sites of the catalyst through the size screening effect, while allowing small molecular CO / O2 to diffuse freely, thereby reducing the direct coverage of the poison on the noble metal surface. (2) Chemical poison resistance of bimetallic systems: Rare earth metals have oxygen storage-release functions, which can dynamically remove adsorbed sulfur / lead species and form stable sulfates or lead oxides. These substances then migrate to the support surface, thereby avoiding blocking the active centers of the precious metals. In addition, the electron transfer between the precious metals and rare earth metals can maintain the reduced state of the precious metals, effectively inhibiting the oxidative deactivation of active sites caused by poisons. (3) Optimization of the surface chemical properties of molecular sieves: The weak hydrophobicity of SAPO-18 or SAPO-34 reduces the adsorption tendency of polar poisons on the catalyst surface; at the same time, the bimetallic loading further weakens the chemical adsorption strength of the poisons through competitive adsorption (such as CO preferentially occupying the active sites). In contrast, due to the lack of physical barriers and chemical synergistic protection, uncoated Pt / TiO2 and Pt-Pr / TiO2 catalysts can directly cover the active metal surface with poisons, resulting in irreversible passivation. It is worth noting that although SAPO-34@Pt / TiO2 has the physical barrier of a molecular sieve, it only carries a single Pt metal and lacks the oxygen buffering effect of rare earth metals, making it unable to dynamically remove adsorbed poisons. Moreover, due to the lack of sufficient electronic effects, its competitive adsorption ability is weak, and poisons are more likely to occupy isolated Pt sites. These factors together lead to its significantly weaker anti-poisoning ability than bimetallic systems (such as SAPO-34@Pt-Pr / TiO2). These results further demonstrate the importance of molecular sieve coating and precious metal-rare earth metal coordinated design in improving anti-poisoning ability.
[0093] Example 5
[0094] A method for preparing a SAPO-34-coated Au-La / TiO2 catalyst comprises the following steps:
[0095] (1) 64.05 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.144 g of chloroauric acid (HAuCl4·3H2O) and 0.561 g of lanthanum nitrate (La(NO3)3·6H2O) were added under constant temperature and stirring at 50°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 3 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 10 hours for aging to form a stable sol. Finally, 2.5 g of hydroxypropyl methylcellulose was added as a binder and stirring was continued for 1 hour to obtain a uniform sol system.
[0096] (2) Place the cordierite honeycomb ceramic support (200 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate and maintain the vacuum for 10 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 90°C for 10 hours. Subsequently, heat the sample to 500°C at a heating rate of 3°C / min and calcine at this temperature for 6 hours to obtain an Au-La / TiO2 monolithic catalyst.
[0097] (3) 1.25 g silica sol, 2.44 g pseudo-boehmite, 2.11 g triethylamine, 4.08 g phosphoric acid, and 15.84 g water were mixed and stirred for 2.5 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Au-La / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 170°C for 4 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 90°C for 10 hours. Finally, the dried sample was heated to 500°C in a 5% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 6 hours, and then switched to a 4% H2 / N2 atmosphere and calcined under the same conditions for 6 hours to obtain a SAPO-34-coated Au-La / TiO2 monolithic catalyst with an Au loading of 0.4 wt.% based on the mass of TiO2 and a La loading of 1.0 wt.% based on the mass of TiO2.
[0098] Example 6
[0099] The only difference from Example 5 is that the steps for preparing the initial gel in step (3) are as follows:
[0100] 3.75 g of silica sol, 7.32 g of pseudo-boehmite, 6.33 g of triethylamine, 12.24 g of phosphoric acid and 47.52 g of water were mixed and stirred for 2.5 hours to form a uniform initial gel.
[0101] Example 7
[0102] The only difference from Example 5 is that the steps for preparing the initial gel in step (3) are as follows:
[0103] 7.5 g of silica sol, 14.64 g of pseudo-boehmite, 12.66 g of triethylamine, 24.48 g of phosphoric acid and 95.04 g of water were mixed and stirred for 2.5 hours to form a uniform initial gel.
[0104] Example 8
[0105] A method for preparing a SAPO-18 coated Ir-Nd / TiO2 catalyst comprises the following steps:
[0106] (1) 35.58 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.220 g of iridium chloride (IrCl3·3H2O) and 0.365 g of neodymium nitrate (Nd(NO3)3·6H2O) were added at a constant temperature of 40°C with stirring. Subsequently, 50 mL of a 2 M aqueous nitric acid solution was slowly added dropwise and the mixture was allowed to react for 3 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 14 hours for aging to form a stable sol. Finally, 1 g of silica sol was added as a binder and stirring was continued for 1.5 hours to obtain a uniform sol system.
[0107] (2) Place the cordierite honeycomb ceramic support (300 mesh) and the sol system of step (1) in a vacuum impregnation apparatus, evacuate the air and maintain the vacuum for 7 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After the impregnation is completed, slowly release the vacuum, remove the sol-loaded support, and dry it at 105°C for 7 hours. Subsequently, heat the sample to 600°C at a heating rate of 2°C / min and calcine at this temperature for 5 hours to obtain an Ir-Nd / TiO2 monolithic catalyst.
[0108] (3) 3.19 g of tetraethyl orthosilicate, 7.86 g of aluminum sulfate, 2.33 g of N,N-diisopropylethylamine, 3.01 g of phosphoric acid and 10.33 g of water were mixed and stirred for 2 hours to form a uniform initial gel. The gel was transferred to a reactor containing a polytetrafluoroethylene liner, and the Ir-Nd / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel and subjected to hydrothermal crystallization reaction at 190° C. for 3 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 105° C. for 7 hours. Finally, the dried sample was heated to 600°C in a 13% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 5 hours, then switched to a 5% H2 / N2 atmosphere and calcined under the same conditions for 5 hours, finally obtaining a SAPO-18-coated Ir-Nd / TiO2 monolithic catalyst with an Ir loading of 1.2 wt.% of the TiO2 mass and a Nd loading of 1.5 wt.% of the TiO2 mass.
[0109] Example 9
[0110] The only difference from Example 8 is that the steps for preparing the initial gel in step (3) are as follows:
[0111] 6.38 g of tetraethyl orthosilicate, 15.72 g of aluminum sulfate, 4.66 g of N,N-diisopropylethylamine, 6.02 g of phosphoric acid and 20.66 g of water were mixed and stirred for 2 hours to form a uniform initial gel.
[0112] Example 10
[0113] 15.95 g of ethyl orthosilicate, 39.31 g of aluminum sulfate, 11.65 g of N,N-diisopropylethylamine, 15.05 g of phosphoric acid and 51.65 g of water were mixed and stirred for 2 hours to form a uniform initial gel.
[0114] Example 11
[0115] A method for preparing a SAPO-18 coated Pt-Gd / TiO2 catalyst comprises the following steps:
[0116] (1) 46.27 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.069 g of chloroplatinic acid (H2PtCl6·6H2O) and 0.112 g of gadolinium nitrate (Gd(NO3)3·6H2O) were added under constant temperature and stirring at 70°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 5 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 18 hours for aging to form a stable sol. Finally, 2 g of polyethylene glycol was added as a binder and stirring was continued for 2 hours to obtain a uniform sol system.
[0117] (2) A cordierite honeycomb ceramic support (200 mesh) was placed in a vacuum impregnation apparatus and vacuumed for 9 minutes to allow the sol prepared in step (1) to fully penetrate the pores of the support. After impregnation, the vacuum was slowly released, the sol-loaded support was removed, and dried at 120°C for 6 hours. Subsequently, the sample was heated to 700°C at a heating rate of 4°C / min and calcined at this temperature for 3 hours to obtain a Pt-Gd / TiO2 monolithic catalyst.
[0118] (3) 2.02 g of silica sol, 4.60 g of sodium metaaluminate, 8.24 g of N,N-dimethyl-3,5-dimethylpiperidinium, 6.62 g of phosphoric acid, and 32.24 g of water were mixed and stirred for 2 hours to form a uniform initial gel. The gel was transferred to a reactor lined with polytetrafluoroethylene, and the Pt-Gd / TiO2 monolithic catalyst prepared in step (2) was immersed in the molecular sieve initial gel. A hydrothermal crystallization reaction was carried out at 140° C. for 6 days. After the reaction was completed, the product was repeatedly washed with deionized water until neutral and dried at 120° C. for 6 hours. Finally, the dried sample was heated to 700°C in a 25% O2 / N2 atmosphere at a heating rate of 5°C / min and calcined for 3 hours, then switched to a 7% H2 / N2 atmosphere and calcined under the same conditions for 3 hours to obtain a SAPO-18-coated Pt-Gd / TiO2 monolithic catalyst with a Pt loading of 0.2 wt.% of the TiO2 mass and a Gd loading of 0.3 wt.% of the TiO2 mass.
[0119] Example 12
[0120] The only difference from Example 11 is that the amounts of chloroplatinic acid and gadolinium nitrate added in step (1) are different:
[0121] (1) 46.27 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.173 g of chloroplatinic acid (H2PtCl6·6H2O) and 0.261 g of gadolinium nitrate (Gd(NO3)3·6H2O) were added under constant temperature and stirring at 70°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 5 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 18 hours for aging to form a stable sol. Finally, 2 g of polyethylene glycol was added as a binder and stirring was continued for 2 hours to obtain a uniform sol system.
[0122] Step (3) finally obtains a SAPO-18-coated Pt-Gd / TiO2 monolithic catalyst with a Pt loading of 0.5 wt.% based on the mass of TiO2 and a Gd loading of 0.7 wt.% based on the mass of TiO2.
[0123] Example 13
[0124] (1) 46.27 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.276 g of chloroplatinic acid (H2PtCl6·6H2O) and 0.410 g of gadolinium nitrate (Gd(NO3)3·6H2O) were added under constant temperature and stirring at 70°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the reaction was allowed to react for 5 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 18 hours for aging to form a stable sol. Finally, 2 g of polyethylene glycol was added as a binder and stirring was continued for 2 hours to obtain a uniform sol system.
[0125] Step (3) finally obtains a SAPO-18-coated Pt-Gd / TiO2 monolithic catalyst with a Pt loading of 0.8 wt.% based on the mass of TiO2 and a Gd loading of 1.1 wt.% based on the mass of TiO2.
[0126] Example 14
[0127] (1) 46.27 g of tetraisopropyl titanate was dissolved in a mixed solvent of 150 mL of anhydrous ethanol and 50 mL of acetylacetone. 0.414 g of chloroplatinic acid (H2PtCl6·6H2O) and 0.597 g of gadolinium nitrate (Gd(NO3)3·6H2O) were added under constant temperature and stirring at 70°C. Subsequently, 50 mL of 2 M nitric acid aqueous solution was slowly added dropwise and the mixture was allowed to react for 5 hours to complete the hydrolysis process. After the reaction was completed, the reaction system was allowed to stand at room temperature for 18 hours for aging to form a stable sol. Finally, 2 g of polyethylene glycol was added as a binder and stirring was continued for 2 hours to obtain a uniform sol system.
[0128] Step (3) finally obtains a SAPO-18-coated Pt-Gd / TiO2 monolithic catalyst with a Pt loading of 1.2 wt.% based on the mass of TiO2 and a Gd loading of 1.6 wt.% based on the mass of TiO2.
[0129] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A molecular sieve coated noble metal-rare earth metal / TiO2 monolithic catalyst, characterized in that: include: A composite active component composed of noble metals and rare earth metals, a TiO2 carrier, and a molecular sieve coating layer; The composite active component composed of the noble metal and the rare earth metal is dispersed in the TiO2 carrier, and the molecular sieve coating layer coats the TiO2 carrier.
2. The molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst according to claim 1, characterized in that: The precious metal is selected from at least one of Pt, Pd, Au and Ir, and the rare earth metal is at least one of La, Gd, Nd and Pr; the precious metal loading accounts for 0.2 to 1.5 wt.% of the mass of the TiO2 carrier, and the rare earth metal loading accounts for 0.2 to 2 wt.% of the mass of the TiO2 carrier.
3. A method for preparing a molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst, characterized in that: The following steps are involved: (1) dissolving a noble metal salt, a rare earth metal salt, and a titanium source in a solvent, hydrolyzing and aging the mixture, and then adding a binder to obtain a sol system; (2) loading the sol system onto a ceramic support, followed by drying, solidification, and calcination to obtain a noble metal-rare earth metal / TiO2 matrix; (3) In situ growth of a molecular sieve coating layer on the noble metal-rare earth metal / TiO2 substrate by a hydrothermal method, followed by stepwise calcination in an oxidizing atmosphere and a reducing atmosphere to obtain the molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst.
4. The preparation method according to claim 3, characterized in that The noble metal salt is selected from at least one of chloroplatinic acid, palladium chloride, chloroauric acid and iridium chloride; the rare earth metal salt is selected from at least one of lanthanum nitrate, gadolinium nitrate, neodymium nitrate and praseodymium nitrate; and the binder is at least one of silica sol, polyvinyl alcohol, polyethylene glycol and hydroxypropyl methylcellulose.
5. The preparation method according to claim 3, characterized in that The temperature of the drying and curing in step (2) is 80-120° C., and the temperature of the calcination is 400-700° C.; the temperature of the hydrothermal method in step (3) is 140-200° C., and the reaction time is 2-6 days.
6. The preparation method according to claim 3, characterized in that In step (3) of the segmented calcination, the oxidizing atmosphere calcination conditions are: in an O2 / N2 mixed gas containing an oxygen volume fraction of 3% to 25%, the temperature is raised to 400 to 700°C, and the constant temperature calcination is carried out for 2 to 8 hours; the reducing atmosphere calcination conditions are: in an H2 / N2 mixed gas containing a hydrogen volume fraction of 1% to 7%, the temperature is raised to 400 to 700°C, and the constant temperature calcination is carried out for 2 to 8 hours.
7. The preparation method according to claim 3, characterized in that The molecular sieve material is SAPO-18 or SAPO-34.
8. Use of the molecular sieve-coated noble metal-rare earth metal / TiO2 monolithic catalyst according to any one of claims 1 to 2 in a CO oxidation reaction.
9. A CO catalytic oxidizer, characterized in that: The invention relates to a noble metal-rare earth metal / TiO2 integral catalyst coated with the molecular sieve according to any one of claims 1 to 2.
10. An exhaust gas treatment system for a steel sintering machine, characterized in that: Comprising the CO catalytic oxidizer according to claim 9.
Citation Information
Patent Citations
Monolithic catalyst and preparation and application thereof
CN107694562A
Dry reformation of methane reaction, nickel and cerium containing core-shell structured catalysts therefor and their preparation
CN107921427A
High temperature sintering resistive loading type noble metal catalyst for catalytic oxidation of carbon monoxide and preparation method thereof
CN108452798A
Highly-dispersed supported slurry bed hydrogenation bead catalyst and preparation method thereof
CN109833901A
CO catalytic oxidation catalyst as well as preparation method and application thereof
CN116037202A
Cited By
System and method for synergistically purifying NOx and CO in low-temperature flue gas
CN121155348A
A filter material layered catalyst for catalytic oxidation of flue gas CO and a preparation method and application thereof
CN122499831A
